A Darker Shade of Pale: Webster’s Winter Whiteness - Annaliese CONNOLLY; Lisa HOPKINS (E-REA)
This essay explores the politics of the colour scheme in John Webster’s tragedies The White Devil and The Duchess of Malfi. On the face of it, we are offered a clear and absolute opposition between black and white in which black, predictably, is bad, and white, equally predictably, is good. We argue, however, that it is actually white which is represented as the more sinister of the two colours, for reasons connected to the plays’ interest in the bodies and behaviour of rulers, specifically James I’s scheme for the annexation of Russia and his reburial of his mother, Mary, Queen of Scots.Reading the plays in relation to these two contemporary events, we argue that in his two great tragedies Webster prises open the instability of the term “white” to lay bare a tension between the spiritual and the material which reveals the darker side of whiteness.